Possible associations between recovery aerobic training and increasing the length of telomeres - D. M. Aronov (Российский кардиологический журнал)
It is known that in recent decades, methods of cardiac rehabilitation have been widely used in patients after acute myocardial infarction, coronary syndrome and cardiac operations. The main active factor in cardiac rehabilitation is a program of physical training. On the other hand, it has been established that physical training and/or sufficient physical activity positively affects the length of human telomeres. It is assumed that under the influence of cardiac rehabilitation, the improvement in the course of the disease may be due to an increase in telomere length. We found studies with such positive associations. This primarily concerns people with prediabetes, overweight, multiple risk factors. We established the importance of training in physically active people, athletes, especially with great sports experience. It seems promising to perform studies (training/telomeres) in patients with history of acute myocardial infarction, acute coronary syndrome and cardiac surgery.